Green Technology Innovations for Carbon Footprint Reduction in the Restaurant Industry: A Systematic Review - Shu-Yen Yang; Chien-Er Huang; John Kennedy Mwangi; Justus Kavita Mutuku; Guo-Ping Chang-Chien (Aerosol and Air Quality Research)
Abstract Restaurants contribute a significant carbon footprint (CF), with the food service sector responsible for 18% of food-related global CF. This impact arises from energy-intensive processes, carbon-intensive ingredient sourcing, inefficient waste management, and upstream and downstream supply chain activities. Notably, commercial kitchens exhibit carbon footprints 2–5 times greater than those of other commercial spaces. This review synthesizes recent empirical and theoretical literature on carbon footprint reduction strategies in restaurants, with emphasis on the application of life cycle assessment (LCA), IPCC methodologies, and material flow analysis (MFA) across diverse regional contexts. Green technologies such as the integration of solar, biogas, and biodiesel systems have been shown to reduce GHG emissions by 20–75%, while composting and food waste valorization can mitigate methane emissions by up to 30%. Menu-based interventions, including the substitution of beef with plant-based proteins and regionally sourced ingredients, offer substantial emissions reductions at the meal level. Despite these advances, the review identifies persistent challenges, including data inconsistency, underreporting of Scope 3 emissions, and limited adoption of standardized carbon accounting frameworks such as ISO 14064, PAS 2050. The findings highlight the need for harmonized assessment tools, integration of digital monitoring technologies, and cross-sector collaboration to enable consistent benchmarking and guide the sector toward carbon neutrality. This review provides a roadmap for advancing low-carbon transitions through operational, behavioral, and policy-driven interventions in the global restaurant industry. Graphical Abstract